2020
DOI: 10.1038/s41598-020-68931-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of feather follicles reveals candidate genes and pathways associated with pheomelanin pigmentation in chickens

Abstract: Yellow plumage is common in chickens, especially in breeds such as the Huiyang Bearded chicken, which is indigenous to China. We evaluated plumage colour distribution in F1, F2, and F3 populations of an Huiyang Bearded chicken × White Leghorn chicken cross, the heredity of the yellow plumage trait was distinguished from that of the gold plumage and other known plumage colours. Microscopic analysis of the feather follicles indicated that pheomelanin particles were formed in yellow but not in white feathers. to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 72 publications
2
27
0
1
Order By: Relevance
“…The significant interaction of the hematopoietic prostaglandin D synthase (HPGDS) gene in chromosome 3 with the GNG13 gene in chromosome 10 associated with plumage coloration has been revealed in our study. Also, down-regulation of HPGDS was displayed by transcriptome analysis, confirming its association with pheomelanin pigmentation in chickens with yellow plumage (Zheng et al 2020). Also, recently, Fogelholm et al (2020) reported five new candidate genes -CREBBP, WDR24, ARL8A, PHLDA3 and LAD1with putative small trans-acting effects by a combination of QTL mapping and a targeted genetic-genomics approach for plumage color.…”
Section: Functional Enrichment Analysismentioning
confidence: 66%
See 2 more Smart Citations
“…The significant interaction of the hematopoietic prostaglandin D synthase (HPGDS) gene in chromosome 3 with the GNG13 gene in chromosome 10 associated with plumage coloration has been revealed in our study. Also, down-regulation of HPGDS was displayed by transcriptome analysis, confirming its association with pheomelanin pigmentation in chickens with yellow plumage (Zheng et al 2020). Also, recently, Fogelholm et al (2020) reported five new candidate genes -CREBBP, WDR24, ARL8A, PHLDA3 and LAD1with putative small trans-acting effects by a combination of QTL mapping and a targeted genetic-genomics approach for plumage color.…”
Section: Functional Enrichment Analysismentioning
confidence: 66%
“…GO and KEGG enrichment of differentially expressed genes associated with pheomelanin pigmentation in chickens has been reported by Zheng et al . (2020). These authors indicated that metabolic pathways, melanogenesis, cytoplasm and cell–cell signaling are involved in plumage coloration, which is in agreement with the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The future is here as it has been proven by numerous pioneering studies in the chicken selective breeding programme around the world with a various approach such as phenomics, sequencing analysis [78,35], transcriptome analysis [57,94], QTL mapping of complex traits [14,30,20], and genome-wide association study [62,2,30,50]. This study demonstrated the possibility of using a genetic marker in the selective breeding programme of golden Pelung chicken with the addition of conventional approaches like morphometrical analysis and phenotypes observation.…”
Section: Diagnostic Genotyping Of G Gallus Tyr Genementioning
confidence: 99%
“…The plumage pigmentation depends on several pigments, including carotenoid, melanin (eumelanin and pheomelanin), porphyrins, avins, psittacofulvins, pterins, purines, and turacin[26, 16,24, 76,20,94]. The two most common and widely found among birds, in particular chickens, are melanin and carotenoid.…”
mentioning
confidence: 99%